2016
DOI: 10.1021/acs.langmuir.6b02937
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Understanding of the Penetration of Functionalized Gold Nanoparticles into Asymmetric Membranes

Abstract: In this work, the interactions between surface-functionalized gold nanoparticles (AuNPs) and asymmetric membranes and the associated cytotoxicity were explored by coarse-grained molecular dynamics simulations. Simulation results show that the surface chemistry of AuNPs and the asymmetry of lipid membranes play significant roles. AuNPs with different signs of charges spontaneously adhere to the membrane surface or penetrate the membrane core. Also, the asymmetric distribution of charged lipids in membranes can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 60 publications
3
58
1
Order By: Relevance
“…The authors believed that the cationic Au NPs diffused directly inside the cells by disrupting the cell membrane . This postulation was further verified in several other publications. , Interaction of surface functionalized NPs leads to the damage of the integrity of cell membrane and results in pore generation. Other than the surface charge, the ligand interaction (after surface functionalization) also costs in variation in toxicity assessment. , Peetla et al studied the effect of the molecular structure of cationic ligand on the cellular uptake through a model membrane.…”
Section: Effect Of Different Physicochemical Properties In the Cytoto...mentioning
confidence: 99%
“…The authors believed that the cationic Au NPs diffused directly inside the cells by disrupting the cell membrane . This postulation was further verified in several other publications. , Interaction of surface functionalized NPs leads to the damage of the integrity of cell membrane and results in pore generation. Other than the surface charge, the ligand interaction (after surface functionalization) also costs in variation in toxicity assessment. , Peetla et al studied the effect of the molecular structure of cationic ligand on the cellular uptake through a model membrane.…”
Section: Effect Of Different Physicochemical Properties In the Cytoto...mentioning
confidence: 99%
“…60 It was also claimed that the charged ligand transfer across the membrane core and the subsequent membrane-spanning conguration was a rare event difficult to sample with coarse-grained simulations, and which was more appropriately evidenced using biasing simulation techniques 25,42 or asymmetric charged membranes. 40 More insights into the conformational changes undergone upon complex binding and intercalation in the bilayer inner region can be gained from the radius of gyration of the complex projected perpendicular and parallel to the bilayer surface R gxy,c R gz,c (Fig. 7).…”
Section: Pec-dppc Bilayer Interactionmentioning
confidence: 99%
“…An increased hydrophobic moiety decreased the lateral pressure required for the bilayer rupture and rendered the membrane more susceptible to mechanical stress. 36 According to atomistic and coarse-grained molecular dynamics simulations of the inorganic particles protected via amphiphilic ligands, 25,[37][38][39][40][41][42][43] these complexes could stably adhere to zwitterionic lipid bilayers and attained eventually the socalled "snorkeling" conformation, characterized by the nanoparticles embedded in the hydrophobic bilayer core and the charged ligands anchored to the charged moiety of both bilayer leaets. The complex bound initially to the bilayer via electrostatics, and the transition from this state to the snorkeling conguration proceeded through several distinct metastable congurations.…”
Section: Introductionmentioning
confidence: 99%
“…This external potential could affect the interaction between the NPs and the membrane, especially the interaction between charged NPs and the polar membrane. For example, it has been shown that the change of the charge densities on the NPs may induce internalization of nanoparticles into cells through different pathways, such as passive translocation for nanoparticles with low charge density, or endocytosis for high charge density ( Figure a) …”
Section: Modeling and Simulation Of Ncs Delivery Through Biological Bmentioning
confidence: 99%